FIT AND PROPER TEST FOR PUBLIC THE OFFICIALS CANDIDATE PERSPECTIVE ON CONSTITUTIONAL ASPECTS - I Ketut Bayu Pawana (Fakultas Hukum Universitas Mataram, 2014)
Constitution Amendments in 1999-2002, significantly changing the constitutional system of Indonesia. One of amendments aspect in constitution that is more empowering Parliament functions, beside their main function there is a new parliament authority that is involvement in the determination of public officials. Such Involvement is limited by the authority of “election” and “consent”. In fact, the Law Number 3 Year 2009 on the Supreme Court and the Law Number 18 Year 2011 on the Judicial Commission setting up the two forms of authority of the House of Representatives that is “choosing“ to the fit and proper test mechanisms. The emergence acted upon the authority of the House of Representatives for the fit and proper test for public officer candidate constituted by the strengthening of the role and functions of Parliament are given by the Constitution, mechanism of checks and balances that govern the relationship between the state institutions are equal and mutually control each other. Fit and proper test is the determination mechanism of public officials by the House of Representatives. However, the suitability of the authority of Parliament to implement fit and proper tests of public officials candidate of the Constitution of 1945 stipulated NRI deviant or contrary to Law Number 3 Year 2009 on the Supreme Court and the Law Number 18 Year 2011. Constitution mandate only on the authority to give consent but by Law Number 18 Year 2011 and Law Number 3 Year 2009 is lead up to the authority to choose by fit and proper test mechanism.Keywords: Authority Parliament and Fit and Proper Test